Synergy of CO2 Storage and Oil Recovery in Different Geological Formations: Case Study in the Baltic Sea. (July 2017) - Shogenov, Kazbulat; Shogenova, Alla; Gei, Davide; Forlin, Edy
Abstract: Pilot project for CO2 storage and CO2 -EOR/EOR+ in different geological formations including two scenarios is proposed for Latvian offshore structure E6. The first "two wells and possible fault-leakage" scenario proposed CO2 storage in the Cambrian Deimena Formation and oil recovery from the Upper Ordovician Saldus Formation. One common injection well and possible fault leakage to the oil reservoir are considered as a profit. The second "three wells and no leakage" scenario, includes additional CO2 injection well to oil reservoir. A surplus for both scenarios is increased CO2 storage capacity. The new pilot project idea supports exploitation of small oil deposits in the Baltic Region.